Perlindungan Hukum Pelaku Usaha dalam Sengketa Kontraktual Pengadaan Barang dan Jasa Konstruksi Pemerintah Ditinjau dari Aspek Hukum Perdata - Mohammad Adzan (JISPENDIORA Jurnal Ilmu Sosial Pendidikan Dan Humaniora, 2024)
The purpose of this study is to identify legal protection for business actors in procuring construction goods and services in the government sector by reviewing various civil aspects. This study applies normative legal analysis with a descriptive analytical nature. The approach applied is legislation. The data required in this study were obtained through literature studies, field studies, and interviews. Data processing and analysis efforts were carried out using qualitative analysis. The analysis of legal protection shows that legal protection is divided into preventive and repressive legal protection for the government (PA/KPA/PPK) and the provider (private sector). Preventive legal protection aims to prevent defense between the government as a service user and the provider of construction goods/services. This prevention is realized in the form of clear regulations, transparency in the procurement process, and the existence of strict monitoring and evaluation mechanisms. In addition, the contract documents drawn up must fulfill legal certainty, justice, and equality between the parties. This preventive aspect is very important for the procurement process to run efficiently, and minimize the potential for abuse, corruption, and default by either party. Meanwhile, repressive legal protection becomes crucial when a breach or violation occurs in the procurement process or implementation of a contract. In this case, the aggrieved party can pursue legal action through dispute resolution mechanisms, including public courts, arbitration, and alternative dispute resolution (ADR). The government, as the service user, must also comply with civil law principles if it violates the agreement. Therefore, this study reinforces the importance of a firm legal basis and fair settlement procedures to ensure trust between the private sector and the government in the construction sector.